The immune response to SARS-CoV-2 in COVID-19 as a recall response susceptible to immune imprinting A prospective cohort study - Alvarez-Sierra, Daniel (Clinical immunology (Orlando, Fla.), 2025)
Copyright © 2025 The Authors. Published by Elsevier Inc. All rights reserved.